The Interplay of Power, Incentives, Academic Freedom, and Gender Equity | AAUP
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.

Developing resilient leaders: a training for students - Jansen, Amy L.; Wieland, Alice (Journal of Leadership Education, 2024)
This assignment is designed to enhance resilience among students in leadership courses. It leverages the US Army’s Master Resilience Training (MRT) framework and positive psychology to develop resiliency skills.A three-part experiential workshop integrates academic readings (providing a foundation of resilience concepts), explores the influence of personal identities on leadership and connects leadership skills with resilience concepts.Participants reflect on self-awareness tools and positive psychology and create personalized action plans. Participants' resilience skills are enhanced with their personalized resiliency plan.The program provides a structured approach to resilience training, which can be integrated into university curriculums. Students gain self-awareness and psychological tools to manage challenges, which are valuable for personal growth and professional development. There is a persistent gender gap in leadership, and for women to attain greater parity in leadership positions, resilience skills are imperative. By focusing on identity-related factors, the program prepares future leaders for challenges in attaining leadership positions.This program is uniquely tailored for students aspiring to leadership positions, with an emphasis on the role of identity, such as gender, in leader emergence and overcoming related challenges.
Keywords: dept.lib; peer-reviewed

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

With Death, an Orange Segment Between Our Teeth, poems by Marie-Claire Bancquart - Bancquart, Marie-Claire (Orison Books, 2023)
With Death, an Orange Segment Between Our TeethMarie-Claire BancquartTranslated from the French by Wendeline A. Hardenberg *Available for pre-order.* Orison Bookspaper / 178 pp. / $18.00bilingualISBN: 978-1-949039-42-9Distributed to the trade by Itasca Books952-223-8373 / orders@itascabooks.comPublication Date: November 7, 2023 ABOUT THE BOOK Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic. In her poetry, she combines an erudite vocabulary and references to classical literature with an earthy sensibility and a fascination with experiencing the smallest moments of everyday life fully. The deceptive simplicity of her poems lays bare the mysteries underlying the world we inhabit and our very existence. Wendeline A. Hardenberg’s careful and skillful translations are sure to broaden the audience for this significant poet as yet too little known outside of France. PRAISE Deeply philosophical, these poems, originally published in French when the author was in her seventies, focus on the meaning of existence. The poet reminds us that our lives—“seven liters of water wrapped in skin”—are “small,” but “the universe [is] in us / us in the universe.” From our “ephemeral perch on the earth,” writing achieves a kind of immortality, producing “a few words warmed by the journey, / that scatter outside, vouching / that you gave them a little extra life.” Readers will be grateful to Hardenberg for carefully shepherding these provocative poems into English. —Nancy Naomi Carlson, recipient of The Oxford-Weidenfeld Translation Prize Strange and wonderful translations of strange and wonderful poems... Marie-Claire Bancquart’s voice is utterly unique; her poems—by turns lyrical and jarring, mystical and forthright, tender and brutal—sing and clamor in your head long after you’ve read them. Like their French originals, Hardenberg’s excellent translations glitter and dart and unsettle; they dodge like wrestlers, then they grab you by the throat and won’t let go. This is rich writing to come back to again and again; each time you’re ambushed by some startling image or phrase or notion that you hadn’t noticed before. A vital book, both in the sense of its aliveness and its urgency.—Bill Johnston, recipient of The PEN Translation Prize ABOUT THE AUTHOR & TRANSLATOR Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic, as well as a Professor Emerita of French literature at the Sorbonne. Her final book, De l'improbable, précédé de Mo(r)t, was published by Éditions Arfuyen in 2020. Wendeline A. Hardenberg studied at Smith College and Indiana University, where she earned master’s degrees in Comparative Literature with a focus on translation and Library Science. She is the translator of numerous books, including The Bookshop of Forgotten Dreams by Emily Blaine, Will You Ever Change? by Aurélie Valognes, and Project Anastasis by Jacques Vandroux. Hardenberg’s translations have been published in Asymptote, Columbia Journal, Metamorphoses, Tupelo Quarterly, Two Lines, and other places. She lives in New Haven, Connecticut. SAMPLE POEM Close The blackberriesare clotted profusely in the bushes we are so close to the secret of this worldthat it seems to be awaitingjusta small steplike onto a balcony, to smell a flower. We don’t move that would be to wound the beingalmost managing to bein view of the fruits’ black boiling.
Keywords: dept.lib; literary-poetry

A Comparison Between "Fan Fiction" and "Professional Fan Fiction" - Clerc, Sue (2006)
Keywords: dept.lib; faculty_collection; sabbatical_report

Colonel James Bowie. - Holmer, Paul L. (1995)
Keywords: dept.lib; faculty_collection; sabbatical_report

The Pharos: The Ancient Lighthouse of Alexandria, Egypt. - Clarie, Thomas C. (1990)
Keywords: dept.lib; faculty_collection; sabbatical_report

Statistical Analysis of the Holdings, Circulation and Acquisitions of the Buley Library Book Collection. - Kobus, Julia (1988)
Keywords: dept.lib; faculty_collection; sabbatical_report

Connecticut news handbook. (Connecticut Information Co)
Publication Title: Connecticut news handbook.
Keywords: Chronology; Connecticut; History; Indexes; Periodicals; Periodicals; Connecticut; Periodicals; Hartford courant; dept.lib; faculty_collection

Will You Ever Change? - Valognes, Aurélie (Amazoncrossing, 2017)
Keywords: Domestic fiction; French; dept.lib; faculty_collection

Fighting the Current: The Rise of American Women's Swimming, 1870-1926 - Bier, Lisa (McFarland & Co., 2011)
"This book describes the origins of women's competitive swimming in the United States. Women faced many obstacles to safe swimming opportunities, including restrictive beliefs about physical abilities, access to safe clean water, bathing suits that did not allow for movement, and opposition from official sporting organizations. This book is a testament to how far female athletes have come"–Provided by publisher.
Keywords: Ederle; Gertrude; 1906-2003; Olympic Games (7th : 1920 : Antwerp; Belgium); Olympic Games (8th : 1924 : Paris; France); Swimming for women; History; History; Swimming; United States; dept.lib; faculty_collection

Saints, Clergy, and Other Religious Figures on Film and Television, 1895-2003 - Paietta, Ann Catherine (McFarland & Co., McFarland & Company, 2005)
"This work details over 900 films and TV series made from the 1890s through 2003 in which a religious figure plays a prominent or recurring role, or in which a character poses as a religious figure"–Provided by publisher.
Keywords: Catalogs; Catalogs; Television programs; Saints in motion pictures; Clergy in motion pictures; Saints on television; Clergy on television; Religion in motion pictures; Religion on television; Motion pictures; dept.lib; faculty_collection

American Indian and African American People, Communities, and Interactions an Annotated Bibliography - Bier, Lisa (Praeger, 2004)
Interest in this topic is growing rapidly, both as a field of academic research and as people with African American and American Indian backgrounds voice interest in their heritage. Materials on this topic are often difficult to locate because of the ways that libraries and research databases organize information. This bibliography is the first of its kind and strives to make researching this understudied topic easier. This volume will serve as an important research tool in this area. This bibliography features books, articles, Web sites, and videos containing information on interactions betwe
Keywords: Bibliography; Bibliography; African Americans; Bibliography; Indians of North America; History; Mixed descent; Relations with Indians; United States. Army. Cavalry; 10th; dept.lib; faculty_collection

A Compendium of Faculty Research and Scholarship - Clarie, Thomas C. (Southern Connecticut State University, 1997)
Keywords: Bibliography; Connecticut; dept.lib; faculty_collection

LC MARVEL: A Guide - Cavanagh, Shirley B. (1995)
Keywords: Southern Connecticut State University; Internet; dept.lib

A Comprehensive, Annotated Bibliography on Mahatma Gandhi - Pandiri, Ananda M. (Greenwood Press, 1995)
Keywords: Bibliography; Gandhi; Mahatma; 1869-1948; dept.lib; faculty_collection

Buley Library Connecticut Room Collection; Holdings List - Hilton C Buley Library; Clarie, Tom; Bennett, Claire (Southern Connecticut State University. Hilton C. Buley Library. Reference Department, 1986)
Publication Title: Buley Library Connecticut Room Collection; holdings list
Keywords: Bibliography; Catalogs; Library catalogs; Connecticut; dept.lib; faculty_collection

Occult/Paranormal Bibliography: An Annotated List of Books Published in English, 1976 Through 1981 - Clarie, Thomas C. (Scarecrow Press, 1984)
English-language books published or reissued between 1976-1981. Arranged alphabetically by authors. Asterisks indicate excellence. Author, title, and subject indexes.
Keywords: Bibliography; Bibliography; Parapsychology; Occultism; dept.lib; faculty_collection

New Haven in 1884 - Shumway, Floyd M.; Hegel, Richard (New Haven Colony Historical Society, 1984)
Keywords: History; New Haven (Conn.); dept.lib; faculty_collection

New Haven: An Illustrated History - Shumway, Floyd M.; Hegel, Richard; New Haven Colony Historical Society (Windsor Publications, 1981)
Keywords: Description and travel; History; New Haven (Conn.); New Haven (Conn.); dept.lib; faculty_collection

Occult Bibliography: An Annotated List of Books Published in English, 1971 Through 1975 - Clarie, Thomas C. (Scarecrow Press, 1978)
Keywords: Bibliography; Bibliography; Parapsychology; Occultism; dept.lib; faculty_collection

Finis E. Engleman: A Biographical Sketch - Hegel, Richard (Department of Instructional Services, Southern Connecticut State College, 1975)
Keywords: Engleman; Finis Ewing; 1895-; dept.lib; faculty_collection

Nineteenth-Century Historians of New Haven. - Hegel, Richard (Archon Books, 1972)
Keywords: 19th century; New Haven (Conn.); Connecticut; Historiography; History; New Haven; dept.lib; faculty_collection

NHSTC: The Growing Community College for the Greater New Haven Area - Buley, Hilton C. (INFO, 1959)
Keywords: Community colleges; Connecticut; History; dept.lib; faculty_collection

Exploring the Use of Common Strict Search Criteria in Nursing Literature Searches - Truex, Eleanor Shanklin; Spinner, Emily; Hillyer, Jean; Ettien, A'Llyn; Wade, Sarah; Calhoun, Courtney; Wolf, Grace; Hedreen, Rebecca; Heimlich, Layla; Nickum, Annie; Vonderheid, Susan C. (Nurse Educator, 2023)
Background: Health sciences librarians and nursing journal contributors have expressed concern about the impact of using strict parameters when searching the literature. Purpose: The purpose of this study was to explore the use of strict search criteria (eg, 5-year rule, “nurse as author”) by direct care nurses and nursing students. Methods: Fourteen online focus groups were conducted with 54 participants: direct care nurses, health sciences librarians, nursing faculty, and nursing students. Nursing faculty and health sciences librarians were included as participants to add perspective to the origins and effects of the use of stringent search criteria. Results: The majority of the nurses viewed the 5-year rule and nurse as author search limits favorably, while noting that a strict date range may hamper successful searching. Librarians viewed these search criteria more unfavorably but recognized the value of topic-appropriate search limits. Conclusion: Reliance on strict limits can be detrimental to pertinent results; however, appropriate use is essential for relevant results. Pedagogy focused on searching the nursing literature needs to emphasize that limits are tools to be used judiciously.
0 citations (Crossref) [2023-10-31] SCSU link: https://ovidsp-ovid-com.scsu.idm.oclc.org/ovidweb.cgi?T=JS&CSC=Y&NEWS=N&PAGE=fulltext&D=ovft&AN=00006223-900000000-98854&PDF=y
Keywords: dept.lib; peer-reviewed

CT Fishing Report Occurrences - Hedreen, Rebecca; Grace, Sean (Zenodo, 2021)
Dataset of gamefish occurrences as compiled from the Connecticut Fishing Report (2006-2018) and Trophy Fish Report (2009-2018), both published by the Connecticut Department of Energy and Environmental Protection. Compiled as thesis project by Rebecca Hedreen for a Masters of Science in Biology from Southern Connecticut State University, with advisor Dr. Sean Grace.
Keywords: Connecticut; Long Island Sound; coastal fisheries; data collections; dept.bio; dept.lib; estuarine fisheries; fish catch statistics; game fish; geographical coordinates; geographical distribution; sport fishing statistics

Miki Gets Dressed Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl, 2021)
Keywords: dept.lib

Sharing: A Pull-the-Tab Book Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Pull and Play: Pacifier Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

SURPRISE! Slide and Play Shapes Translated by Wendeline Hardenberg - Fouquier, Elsa (Twirl, 2021)
Keywords: dept.lib

Animal Friends 1 2 3 Translated by Wendeline Hardenberg - Loupy, Christopher (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Rain Forest Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Space Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl, 2021)
Keywords: dept.lib

Little Bug on the Move Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Matching Game Book: Bugs and Other Little Critters Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Dinosaurs and the Prehistoric World Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Oceans and Marine Life Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Polar Animals Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2021)
Keywords: dept.lib

Mr. Lion's New Hair! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl, 2021)
Keywords: dept.lib

Magnetology: Animals Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

The Pop-Up Guide: Vehicles Translated by Wendeline Hardenberg - Poulain, Maud (Twirl, 2021)
Keywords: dept.lib

This Book Can Do Anything Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2021)
Keywords: dept.lib

Pull and Play Books: Let's Be Safe Translated by Wendeline Hardenberg - Henand, Alice Le (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Vehicles and Transportation Translation by Wendeline Hardenberg (Twirl, 2021)
Keywords: dept.lib

Do You Know?: Space and Sky Translated by Wendeline Hardenberg (Twirl, 2021)
Keywords: dept.lib

Ultimate Spotlight: Volcanoes Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2022)
Keywords: dept.lib

Crack-Crack! Who Is That? Translated by Wendeline Hardenberg - Mory, Tristan (Twirl, 2022)
Keywords: dept.lib

Do You Know?: Earth and Nature Translated by Wendeline Hardenberg - Benoist, Cécile (Twirl, 2022)
Keywords: dept.lib

Do You Know?: Animals of Land, Sea, and Air Translated by Wendeline Hardenberg - Babin, Stéphanie (Twirl, 2022)
Keywords: dept.lib

The Ultimate Book of Water Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl, 2022)
Keywords: dept.lib

What About: Science Translated by Wendeline Hardenberg - Fichou, Bertrand (Twirl, 2022)
Keywords: dept.lib

The Pop-Up Guide: Natural Wonders Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl, 2022)
Keywords: dept.lib

The Bookshop of Forgotten Dreams: A page-turning opposites attract romantic comedy! Translated By Wendeline Hardenberg - Blaine, Emily (One More Chapter, 2021)
Keywords: dept.lib

From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg - Aubry, Gwenaëlle (Columbia Journal, 2021)
From La Folie Elisa By Gwenaëlle Aubry Translated by Wendeline A. Hardenberg
Section: Translation
Keywords: dept.lib

“The Master of Scents” * Fiction * By Vincent Ravalec * Translated by Wendeline A. Hardenberg - Ravalec, Vincent (Aromatica Poetica, 2022)
He was the Master of Scents. He ruled over them, classified them, harnessed them, recombined them, invented them, and above all took care of their dis...
Keywords: dept.lib

Social bookmarking for organization, discovery, and publication - Hedreen, R.C. (Journal of Library and Information Services in Distance Learning, 2006)
Keywords: dept.lib; ⛔ No DOI found

Doing more with more: Systems, services and emerging technologies - Thomas, L.C. (An Overview of the Changing Role of the Systems Librarian: Systemic Shifts, 2010)
Journal Abbreviation: An Overv. of the Chang. Role of the Syst. Libr.: Syst. Shifts
Keywords: Emerging technologies; dept.lib

Handheld libraries 101 using mobile technologies in the academic library - Kosturski, K.; Skornia, F (Computers in Libraries, 2011)
Keywords: dept.lib; ⛔ No DOI found

Trendspotting 2011 - Thomas, L.C. (Journal of Web Librarianship, 2011)
0 citations (Crossref) [2023-10-31]
Keywords: dept.lib

Expanding and Improving Our Library’s Virtual Chat Service: Discovering Best Practices When Demand Increases - Fruehan, Parker; Hellyar, Diana (Information Technology and Libraries, 2021)
With the onset of the COVID-19 pandemic and the ensuing shutdown of the library building for several months, there was a sudden need to adjust how the Hilton C. Buley Library at Southern Connecticut State University (SCSU) delivered its services. Overnight, the library’s virtual chat service went from a convenient way to reach a librarian to the primary method by which library patrons contacted the library for help. In this article, the authors will discuss what was learned during this time and how the service has been adjusted to meet user needs. Best practices and future improvements will be discussed.
6 citations (Crossref) [2023-10-31] Number: 3
Keywords: dept.lib; peer-reviewed

Feelings Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
It’s never too early to encourage children to talk about how they feel. This newest title in the Pull and …
Keywords: dept.lib

Who Lives Where? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Sliding panels of animals near and far make for a delightful and satisfying format for matching game fun! Each of …
Keywords: dept.lib

Construction Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Bumpy roads, rough wood beams, and smooth concrete—there’s so much to discover in this Touch and ExploreTM book that’s all …
Keywords: dept.lib

Super Mazes in Space! Translated by Wendeline Hardenberg - Méhée, Loïc (Twirl Books, 2019)
Ten incredible mazes combine with a space adventure to provide a stellar game book for every puzzle-solving kid! Comics artist …
Keywords: dept.lib

Cars Translated by Wendeline Hardenberg - Krasinski, Geraldine (Twirl Books, 2019)
Turn a wheel to see cars of yesteryear, slide a new car onto a car carrier, pull a tab to …
Keywords: dept.lib

Body Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2019)
Big, sturdy tabs to push and pull make for great learning fun in this brand-new nonfiction series. Preschool children learn …
Keywords: dept.lib

Pirates Translated by Wendeline Hardenberg - Adams, Ines (Twirl Books, 2019)
Heave ho! Set sail on a high-seas adventure with swashbuckling pirates in search of treasure in this new Magnetology™ title. …
Keywords: dept.lib

Savanna Animals Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Take a trek into the wild . . . • Hunting for food • Building homes • Keeping cool • …
Keywords: dept.lib

Astronauts Translated by Wendeline Hardenberg - Dussaussois, Sophie (Twirl Books, 2019)
Count down to an incredible voyage! • Learning to pilot a spacecraft • Getting used to being weightless • Going …
Keywords: dept.lib

Jungle Animals Translated by Wendeline Hardenberg - Mazas, Marie (Twirl Books, 2019)
The shaggy fur of a sloth, the scaly skin of an iguana, and the rough hide of a tapir—there’s so …
Keywords: dept.lib

Bathtime Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2019)
Little Crocodile, Little Monkey, and all their friends can think of a lot more things they’d rather do than take …
Keywords: dept.lib

Ultimate Book of Planet Earth Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2019)
The internationally successful Ultimate Book series expands its scope to embrace-very appropriately-the whole world! The Ultimate Book of Planet Earth …
Keywords: dept.lib

Badadoom Badabump! Translated by Wendeline Hardenberg - Baou, Bartélémi (Twirl Books, 2019)
Inspiring imagination and encouraging hours of creative play, Badaboom Badabump! is an innovative play set that not only includes a …
Keywords: dept.lib

Mealtime Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Little Crocodile, Little Monkey, and all their friends may not like to try new foods or know what to do …
Keywords: dept.lib

Brothers and Sisters Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Little Crocodile, Little Monkey, and all their friends have siblings—siblings who take their things, make a mess, or just get …
Keywords: dept.lib

Mr. Lion Dresses Up! Translated by Wendeline Hardenberg - Teckentrup, Britta (Twirl Books, 2020)
How exciting! Mr. Lion has been invited to a party! But what will he wear? A handsome suit . . …
Keywords: dept.lib

Trains Translated by Wendeline Hardenberg - Prénat, Sophie (Twirl Books, 2020)
All aboard! Chock-full of fascinating facts, Ultimate SpotlightTM Trains offers young readers a closer look into the marvelous world of …
Keywords: dept.lib

Animals at Night Translated by Wendeline Hardenberg - Hedelin, Pascale (Twirl Books, 2020)
The fluffy feathers of an owl, the bumpy skin of a toad, and the thick fur of a river otter—there’s …
Keywords: dept.lib

Miki Takes a Bath Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Splish-splash! Miki’s taking a bath! Bathtime couldn’t be more fun with Miki showing how it’s done in this delightful pop-up …
Keywords: dept.lib

The Ultimate Book of Horses Translated by Wendeline Hardenberg - Laboucarie, Sandra (Twirl Books, 2020)
Horses are amazing creatures! The Ultimate Book of Horses provides hours of hands-on discovery and includes age-appropriate information on the …
Keywords: dept.lib

Magnetology: Vehicles Translated by Wendeline Hardenberg - Baumann, Anne-Sophie (Twirl Books, 2020)
Take a ride—whether it’s on a boat, plane, or on a rocket ship! Kids can use the 45 magnetic pieces included to fill 5 oversized scenes in this Magnetology™ title. The all-in-one play set features fascinating information, just right for its audience, about all types of vehicles: those that travel on the road, on a farm
Keywords: dept.lib

Who Does What? Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
Who gathers honey? Who designs clothes? Who makes lunch for students? So many jobs can be found in this delightful and satisfying sliding panel format for preschoolers. The 36 panels feature jobs in various settings: in the orchestra, at the market, at school, and more! Each new spread offers clues to the right respon
Keywords: dept.lib

Mr. Bear's Birthday Translated by Wendeline Hardenberg - Aracil, Virginie (Twirl Books, 2020)
Mr. Bear is having a birthday party, and everyone is welcome! It doesn’t matter if you’re big, small, don’t have teeth, or are afraid of the dark . . . you’re invited! In this wonderfully illustrated oversize book that celebrates inclusion as well as a special day, Mr. Bear’s Birthday also includes lots of gifts—with f
Keywords: dept.lib

Patience Translated by Wendeline Hardenberg - Le Hénand, Alice (Twirl Books, 2020)
Waiting is not easy, whether it’s waiting to play with a toy or to eat a snack. And Little Kangaroo, Little Cat, and their friends are just not sure that they can be patient. But as their grown-ups show them, being patient doesn’t have to be boring or unbearable. There are many fun things they can do while they wait! C
Keywords: dept.lib

City Mazes Around the World Translated by Wendeline Hardenberg - Babin, Stephanie (Twirl Books, 2020)
From New York City to Tokyo and Berlin to Sydney, the streets of the 15 cities included in this book are filled with a fascinating showcase of local landmarks and awesome attractions. How will you get from the Brooklyn Bridge to Central Park in New York City? Or find your way to Topkapi Palace in Istanbul? Each spread
Keywords: dept.lib

Max Ernst Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Qarrtsiluni Online Literary Magazine, 2011)
Keywords: dept.lib

[Three Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Asymptote, 2012)
Keywords: dept.lib

[Six Poems] Translated by Wendeline Hardenberg - Bancquart, Marie-Claire (Metamorphoses: Journal of the Five-College Seminars on Literary Translation, 2013)
Keywords: dept.lib; ⛔ No DOI found

Heart Collector Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2015)
Finding murderers is just a day on the job for police captain Nadia Barka. But when a mutilated corpse is discovered in an old baptistery, she’s faced with some difficult questions: Who left a young woman’s body in a high-security museum in the middle of the night? And where is the victim’s heart?Barka has no leads, until several days later when unassuming computer technician Julien Lombard comes forward, claiming to have had a premonition of the woman’s abduction and murder. The ensuing investigation turns up nothing, however, and Julien is just as skeptical about his intel as the police are. But, after another woman goes missing, Barka decides to take a chance and trust in Julien’s gift. Does Julien hold the key to preventing another gruesome crime? Working together, can they find the murderer before he steals another heart?
Keywords: dept.lib; faculty_collection

Out of Sorts Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2016)
Ferdinand Brun hasn’t always been a grumpy old man. Many years ago, he was a grumpy young man. Now he’d much rather spend time with his canine companion, Daisy, than any of his nosy neighbors. But as his behavior becomes increasingly peculiar, his daughter grows concerned and begins to consider moving him into a retirement home.In order to maintain his freedom, Ferdinand must submit to an apartment inspection by his longtime enemy, the iron-fisted concierge, Mrs. Suarez. Unfortunately, he’s never tidied up a day in his life. His neighbors, precocious ten-year-old Juliette and vivacious ninety-two-year-old Beatrice, come to the rescue. And once he lets these two into his life, things will never be the same. After an eighty-three-year reign of grouchiness, Ferdinand may finally learn that it’s never too late to start living.
Keywords: Aging; Fiction; Fiction; Families; Fiction; France; Fiction; Man-woman relationships; dept.lib; faculty_collection

Project Anastasis Translated by Wendeline Hardenberg - Vandroux, Jacques (Amazon Crossing, 2016)
As a former soldier, private investigator Jean Legarec is used to high stakes and sharpshooters. But he doesn’t realize what he’s getting into when he agrees to investigate the disappearance of six-year-old Alexandre, the grandson of a highly influential French politician.For a million euros, Legarec launches a dangerous search that will dig deep into some of the darkest corners of European history. With the help of the boy’s beautiful aunt, Béatrice, he uncovers evidence of a modern-day terrorist plot rooted in a long-buried enterprise of the Third Reich. From Paris to Malta to the Vosges forest, a cast of witnesses—including a death camp survivor and former mercenaries—help Legarec piece together a terrifying truth.Yet even then, the PI worries that his own dark past and his undeniable attraction to Béatrice might be clouding the investigation. Can he put the personal aside in order to do his job? And can he free an innocent child from a web of absolute evil?
Keywords: dept.lib; faculty_collection

The Matrix and the Machine Translated by Wendeline Hardenberg - Ravalec, Vincent (Asymptote, 2018)
Keywords: dept.lib

Persephone 2014 Translated by Wendeline Hardenberg - Aubry, Gwenaëlle (Asymptote, 2019)
Keywords: dept.lib

Contemporary Art is Internationally Appealing by Vincent Ravalec, translated by Wendeline A. Hardenberg - Gaffey, Marlee (Tupelo Quarterly, 2018)
The challenge was to make appealing something that was not. To transform this godforsaken city, populated by people as indifferent to art as tourists are to the idea of visiting the only historic building—a vague ruin of a castle—in a glamorous destination. After all, what the Guggenheim did for Bilbao could be reproduced […]
Keywords: dept.lib

Collecting Citations from Text - Hedreen, Rebecca (2020)
Basic steps and scripts used for translating text citations to bibtex files suitable for loading into citation management software or citation analysis scripts. 3 publically available...
Keywords: dept.lib

Exploring virtual librarianship: second life library 2.0 - Hedreen, Rebecca; Johnson, Jennifer L; Lundy, Mack A; Burnette, Peg; Perryman, Carol; van den Brekel, Guus; Jacobson, Jj; Gullett, Matt; Czarnecki, Kelly (Internet Reference Services Quarterly, 2008)
In April 2006, Alliance Library System and Online Programming for All Libraries partnered to start the Second Life Library 2.0 in the online world Second Life and in August 2006 purchased an island on the Teen grid of Teen Second Life. Second Life is a virtual world, a descendant of multiplayer online games. Educational institutions have recently been drawn into Second Life's robust economy and vibrant cultural life. The Second Life Library 2.0 works with librarians from around the world and with other educational partners such as TechSoup, WorldBridges, and the New Media Consortium. Second Life Library 2.0 provides traditional library services such as ready reference, book discussions, and search assistance, but, at heart, it explores what it means to be a virtual library in a virtual world.
11 citations (Crossref) [2023-10-31] Citation Key Alias: pop00099 tex.type: [object Object]
Keywords: Library 2.0; Online Collaboration; Online Education; Second Life; Virtual Librarians; Virtual Libraries; Virtual Worlds; dept.lib

Twitter at the office - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2010)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/077-080-070-112-03X tex.type: [object Object]
Keywords: dept.lib

Subscriptions are us: content, access, & collections - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-350-398-102-179 tex.type: [object Object]
Keywords: dept.lib

Tools of academic library assessment: the user survey - Liebst, Anne; Feinmark, David (Journal of Library Administration, 2016)
Academic libraries are taking a closer look at how well they are serving the needs of their users. As a result assessment activities become more important. In this column, the authors will focus on and describe one major tool of assessment—the user survey. © 2016, Published with license by Taylor & Francis.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-442-307-245-879 tex.type: [object Object]
Keywords: academic libraries; assessment; dept.lib; libraries—evaluation; library administration; library planning; user surveys

The breath of my life: constructing the self in chen ran’s A private life - Hardenberg, Wendeline A (Women's Studies, 2014)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/005-702-343-801-36X tex.type: [object Object]
Keywords: dept.lib

Building blocks for personal brands - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-002-113-520-877 tex.type: [object Object]
Keywords: dept.lib

Design for double rainbow - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/124-582-046-811-968 tex.type: [object Object]
Keywords: dept.lib

Google+ and the commodification of cool - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2011)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-170-969-515-573 tex.type: [object Object]
Keywords: dept.lib

Gone mobile? - Thomas, Lisa Carlucci (Library Journal, 2010)
tex.unique-id: ISI:000283457000013
Keywords: dept.lib; ⛔ No DOI found

Library intranets: trends and enhancements - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/190-515-926-757-166 tex.type: [object Object]
Keywords: dept.lib

Service standards for the Mobile/Social library - Thomas, Lisa Carlucci (Journal of Web Librarianship, 2010)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/125-177-835-426-699 tex.type: [object Object]
Keywords: dept.lib

Technical service outreach strategies for academic libraries - Toce, Jacqueline; Schofield, Cindy (Technical Services Quarterly, 2011)
The model of a library staff divided into technical and informational service divisions remains common-especially among academic libraries. The authors argue that in many ways it is now the technical services division that is best positioned to provide outreach services to a community-whether at the university or municipal level. Maintaining bibliographic access amid the changing information landscape hinges on a clear understanding of systems, metadata, and traditional organizational skills, all home grown in the back rooms of conventional libraries. The authors cite examples of library outreach that emanated from technical service departments and conclude that the sequestered staffs of the past must make themselves indispensible today by sharing their knowledge and talents, offering services to their communities that require their technical expertise, and advance the mission of the library organization. © Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/135-473-790-983-166 tex.type: [object Object]
Keywords: Academic libraries; Catalogers; Cooperative; Outreach; Service; Southern connecticut state university; Technical services; dept.ils; dept.lib

Will You Ever Change? Translated by Wendeline Hardenberg - Valognes, Aurélie (Amazon Crossing, 2017)
Charming, quirky, and funny, this oh-so-relatable novel from the bestselling author of Out of Sorts shines a light on the always-complicated je ne sais quoi of every family’s relationship.As Martine and Jacques Le Guennec prepare for their annual family Christmas dinner, Martine reminds her husband to be on his best behavior. Their son Nicolas is bringing his girlfriend, Jeanne, to their home for the first time, and she doesn’t want Jacques to scare this one off.Jacques has always ruled his roost with patriarchal bravado, and he can’t help but verbally antagonize everyone—especially the wives of his sons. Jeanne, a strong-willed woman who grew up without a father, clashes with the curmudgeon, and she worries that her boyfriend might be too much like his father.It’s all starting to make Martine question everything about her relationship with her husband. And, though she makes that perfectly clear to him, the old dog is not anxious to learn new tricks.When Jeanne saves Jacques’s life, he begins to realize it may be time to change his ways if he wants to hold on to his wife and keep the family close. But is it too late?
Keywords: dept.lib